Love me, love me not. Vol. 5 - Sakisaka, Io; Thistlethwaite, Nancy (Shojo beat manga., 2020)
"Fast friends Yuna and Akari are complete opposites--Yuna is an idealist, while Akari is a realist. When lady-killer Rio and the oblivious Kazuomi join their ranks, love and friendship become quite complicated!... Love and friendship have become quite complicated for these four friends. After dreaming about kissing Yuna, Rio can't stop thinking about her. Meanwhile, Akari pursues Kazuomi, but it seems he's not interested in her?"--Provided by publisher.